Information literacy in Portugal: a theory and practice approach - Silva, Armando Malheiro da (2016)
With this communication we intent to present a project which, although focused on the specific case of Portugal, intents to make a scientific approach of the challenges of the European Higher Education Area (EHEA) and its impact in the field of the information literacy, considering the actual context of the Information Society. The main questions that it intents to answer are: understand how the university students face the new competences required by the creation of the EHEA; know how these students are prepared in terms of information competences, in three different moments, i.e., prior to the university, during the university frequency period and at the end of the university degree. The inter and transdisciplinary approach between the Education, Cognitive Sciences and Information Science are clearly stated in the epistemological and theoretical model that supports it, profiting of the interaction between information needs produced in the educational context and the students informational universe and its dynamics, without forgetting to consider the connections of students informational behaviour with their personal and social context and demands. The study will be performed on a national scale, in order to allow comparisons between regions with different development levels. The sample will include students from both study cycles. The methodology used in this study will be divided in two areas, qualitative and quantitative research. The qualitative research will permit to obtain precious indicators about the students information behaviour, expectations, needs and use of information. The indicators obtained in qualitative research will be used to design questionnaires, which will to be performed in 17 high schools and 17 universities, with an estimated sample of approximately 2000 students. The final result of this research will be the design of an informational behaviour map, at the university level, and the development of a model concerning the promotion of information competences in Portuguese university students.